Potential of phenolic antioxidants - Ružić, Iva (Acta chimica slovenica, 2010)
In vitro studies have shown a link between the consumption of food rich in (poly)phenols, especially flavonoids, and reduced risk of coronary heart diseases. Several flavonoids have been reported to prevent low density lipoprotein cholesterol oxidation in vitro. The aim of our work was to determine antioxidant and radical scavenging activity of flavonoids myricetin,quercetin, rutin, luteolin, apigenin, kaempferol, catechin, epicatechin and epigallocatechin gallate and to study the influence of chemical structure and flavonoid interactions on the ability to inhibit oxidation and scavenge free radicals. Two in vitro methods, i.e. oxidation of â-carotene in an emulsion system and DPPH (1,1-Diphenyl-2-picrylhydrazyl) radical scavenging assay, were applied. In addition, a review of in vivo studies that investigate the effectiveness of food flavonoids in reducing oxidative damage in human body was done and their results were analyzed and compared to in vitro results obtained in our laboratory. Although all tested flavonoids except apigenin showed strong antioxidant and antiradical properties in vitro, these findings can not be completely confirmed from the reviewed in vivo human studies since those results are sometimes contradictoryand inconsistent.
Keywords: antioksidanti; antioxidant; fenoli; flavonoidi; organska kemija